Meningkatkan Hasil Belajar Siswa Kelas IV Pada Mata Pelajaran SBBdP Dengan Menggunakan Model Pembelajaran Kooperatif Tipe Stad di SD Inpres 5 Taipa Laga - Nabilah Muthiah Nabilah; Andi Imrah Dewi; Rangga Putra Boroallo; Kadek Hariana (JURNAL DIKDAS, 2025)
Data collection techniques used include tests, observations, interviews, and documentation. There are two data analysis techniques, namely quantitative data and qualitative data analysis. The results of the research and discussion, it was concluded that the STAD type cooperative learning model can improve the learning outcomes of grade IV students in Arts and Crafts subjects at SD Inpres 5 Taipa Laga. This is evidenced by: 1) The activities of teachers and students during the implementation of the STAD type cooperative learning model in Arts and Crafts learning have increased. This is indicated by an increase in the percentage of teacher and student activity in cycles I and II. Teacher activity in cycle I was 77.77% to 84.44% in cycle II. While student activity in cycle I was 78.88% to 84.44% in cycle II. Observation of teacher and student activities in the application of the STAD type cooperative learning model in SBdP learning went well. 2) Analysis of student learning outcomes showed an increase in student scores and percentage of completion in each cycle. In cycle I, the average score was 60.31 with a classical learning completion percentage of 50% or 8 students out of 16 students who took the test. While in cycle II, the average student score was 68.12 with a classical learning completion percentage of 75% with 12 students out of 16 students who took the test. The application of the STAD type cooperative learning model can increase student learning outcomes by 25% from cycle 1 to cycle II.